New evaluation and modeling procedure for horizontal shear bond in composite slabs - Abdullah, Redzuan; Easterling, W. Samuel (Elsevier, 2009)
A new method for modeling the horizontal shear bond in steel deck-concrete composite slabs is proposed. The method considers the slab slenderness as the strength parameter that affects the accuracy of horizontal shear bond modeling. A calculation procedure called the Force Equilibrium method is developed to generate shear bond stress versus end slips relationship (shear bond property) from bending tests. An interpolation procedure is also presented to estimate the shear bond property curves for slabs of varying slenderness using two sets of bending test data. The shear bond property curves are applied to connector elements of finite element models to model the horizontal shear bond behavior in composite slabs. The results of this study show that the shear bond of composite slabs under bending varies with the slenderness parameter, and hence influences the slab strength and behavior, as well as affecting the accuracy of the finite element analyses. The finite element analyses conducted on slabs with different slenderness utilizing a single shear bond property, which are not varied according to the slenderness parameter, may lead to either safe or unsafe results, depending on the geometry of the slabs.